Problems of Translating Nigerian Authors: The Case of Chinua Achebe’s No Longer at Ease - Ozulu, Ngozi (Meta, 1992)
AbstractEffort was made to identify some specific problems involved in translating Nigerian authors, with Chinua Achebe’s No Longer at Ease as a case study. It was discovered that the translation of some terms or phrases were inadequately rendered in French due to the problem of creating a suitably Africanized French stylistically, semantically, and pragmatically equivalent to its Anglophone counterpart. Hence, the problems encountered and identified were the peculiarity of Nigerian English, aspectual problems and non-uniformity in the orthography of Nigerian Pidgin and of course the existence of regionalized and africanized terms or Africanisms which have not found their ways into the dictionaries.